PERSEPSI GURU PAI TERHADAP PROGRAM SEKOLAH PENGGERAK DALAM MENANAMKAN AKHLAK SISWA DI SMP-IT DARRUL UZMA PICUNG KABUPATEN PANDEGLANG - ihrom; zainal mutaqin, mumu; Rahmi Fauziah, Dewi; M. Muslim (Khidmatussifa: Journal of Islamic Studies, 2025)
This study aims to determine the level of PAI teachers' perceptions of the Movers School Program in an effort to instill student morals. This program is a government initiative that aims to improve the quality of education through a more innovative and character-based approach. In the context of Islamic Religious Education (PAI), the role of teachers is very important in shaping students' morals in accordance with Islamic values. Therefore, this study focuses on how PAI teachers perceive the effectiveness of Sekolah Penggerak Program in supporting their duties in guiding and shaping students' characters. This study used a descriptive qualitative approach with observation, interview, and documentation methods to gain a deeper understanding of teachers' perceptions. The results showed that the majority of PAI teachers have a positive view of this program, as it is considered capable of providing space for the development of students' morals in a more systematic and structured manner. However, there are some challenges in the implementation of the program, such as limited resources and the need to improve teachers' understanding and skills in applying the concepts promoted by the Movers School Program. Therefore, further support from various parties is needed to ensure the success of this program in forming a generation with good morals.